Integrated use of GRACE-derived terrestrial water storage changes and MODIS vegetation indices for RS-based drought monitoring - Cruz, Anjilyn Mae J. (2013)
The Philippine has been experiencing recurring drought events accentuated by the increasing incidence of El Niño phenomenon, particularly in Cagayan Valley Region. To address the negative effects of unpredicted drought events especially with the perceptible climate change, this research developed a methodology for RS-based drought monitoring by integrating 16-day MODFIS Vegetation Indices. (VSs) product with 250-m resolution and monthly Terrestrial Water Storage changes (TWSC) data in 1˚ (111 ?km) grids from NASA?s Gravity Recovery and Climate Experiment (GRACE). Time-series data of TWSC and VI anomalies were statistically analyzed and compared with ground-based measurements of rainfall and water levels from monitoring stations with Cagayan River Basin (CRB) using 3-month running averages cross-correlation analysis. Results showed that changes in ground water and vegetation health as indicated by TWSC and Vis, respectively, have varying correlations and response delays with respect to rainfall and water level changes depending on the condition of wetness or dryness of the prevailing season. However, it was observed that the results of running averages cross-correlation analysis between TWSC and VI anomalies exhibit a trend during drought events-high correlation coefficients coupled with low time lags. This can be used as an indicator of drought onset, duration and spatial distribution. Because of this, the lag-normalized correlation analysis was developed to monitor and characterize the drought periods, and to identify the drought-prone areas in CRB as well. Since the correlation results were limited by the spatial resolutions of the datasets compared owing to the varying and generalized vegetation coverage per pixel, the trend observed can be more precise in characterizing drought events when higher resolution data are used. Drought-sensitive areas in CRB were identified to be range lands located in flat grounds (0-17% slope) and has a soil texture of loam, silty loam, or clay loam based on the cross-correlation analysis, mostly situated at the central part of the river basin. Majority of the barangays identified as drought-prone based on the lag-normalized correlations between 2-year time seriues of TWSC and EVI anomalies are located in Cagayan and Isabela, with total areas of 2595.71 hectares (68321%) in 696 barangays and 3751.02 hectares (56.89%) in 271 barangays, respectively. These provinces are also the most extensively affected by drought events based on actual historical records. The results were also validated using SWAT-simulated soil moisture, 2009 to 2011 rainfall values, and volume of crop production. The trends identified using lag-normalized correlations corresponded very well with the rainfall and crop production records. However, the soil moisture changes did not exhibit good correlation results with the other parameters, mainly due to the limited validation of the simulated values used. Since monitoring schemes usually depend on precipitation-derived indices alone and do not account for groundwater variations, the methodology performed in this study using the RS-based VI datasets and TWSC values was found to provide a reliable means of detecting the onset of droughts and assessing its progression. This in turn can help efforts to mitigate the adverse impacts of droughts to people, economy and environment.